PENGARUH KARAKTERISTIK, KOMPLEKSITAS, DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Khasanah, Nur Lailatul; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2014)
As a form of accountability and transparency to the public, local governments have to make the Local Government Financial Report (LGFR) completed by disclosure. The presence of Government Accounting Standards (GAS) requires the disclosure of certain LGFR items in accordance with GAS. The purpose of this study was to determine the effect of the government characteristics, the government complexity, and audit findings on the level of disclosure LGFR in Central Java 2010-2012. Samples are 35 LGFR in Central Java province each year. The analytical method used is panel data regression using E-views 7.0 software. The results showed that, only the total asset has significantly positive effect on the disclosure level of LGFR and the number of functional differentiation has significantly negative effect. Whereas other variables such as wealth, level of dependence, age, legislature size has no significant effect. Likewise, the audit findings variable has no significant effect on the disclosure level.Â